2013
DOI: 10.1126/science.1239454
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Generation of H 2 by Splitting Water with an Isothermal Redox Cycle

Abstract: Solar thermal water-splitting (STWS) cycles have long been recognized as a desirable means of generating hydrogen gas (H2) from water and sunlight. Two-step, metal oxide-based STWS cycles generate H2 by sequential high-temperature reduction and water reoxidation of a metal oxide. The temperature swings between reduction and oxidation steps long thought necessary for STWS have stifled STWS's overall efficiency because of thermal and time losses that occur during the frequent heating and cooling of the metal oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
246
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 311 publications
(252 citation statements)
references
References 25 publications
6
246
0
Order By: Relevance
“…(2) and (3), favor lower temperatures in order to ensure a complete oxidation of ceria [12] with a typical temperature range of around 700 Ke1100 K. The temperature difference between the two steps requires solid phase heat recovery in order to maintain a high solar-to-fuel efficiency [14], which is difficult to realize and increases the system complexity. Therefore, isothermal cycling has been proposed [16,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…(2) and (3), favor lower temperatures in order to ensure a complete oxidation of ceria [12] with a typical temperature range of around 700 Ke1100 K. The temperature difference between the two steps requires solid phase heat recovery in order to maintain a high solar-to-fuel efficiency [14], which is difficult to realize and increases the system complexity. Therefore, isothermal cycling has been proposed [16,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Muhich et al demonstrated that the hercynite cycle can be performed at an isothermal condition for M = Co [2] and achieved reducing the energy loss due to the difference between the reduction and oxidation temperatures. However, the microscopic mechanism of these reactions are not clarified yet.…”
Section: Introductionmentioning
confidence: 99%
“…Co, Ni, Zn, Cu, and Mn substitutions into ferrite spinel structures have recently been used in successful hightemperature H 2 O/CO 2 splitting, suggesting that the M x Fe 3-x O 4 form of these mixed oxides is particularly active (Kodama et al, 2008;Gokon et al, 2011;Kodama et al, 2005;Rydén et al, 2011;Alvani et al, 2005;Tamaura et al, 1998;Hwang et al, 2004;Miller et al, 2008;Fresno et al, 2009;Fresno et al, 2010;Arifin et al, 2012;Gokon et al, 2008b;Agrafiotis et al, 2015;Goikoetxea et al, 2016;Lorentzou et al, 2014;Cha et al, 2007;Kodama et al, 2002). Other spinel structures are also of interest, such as the ''hercynite cycle" (Muhich et al, 2013 (Haussener et al, 2010c). Gokon et al, 2008a;Han et al, 2007;Miller et al, 2008;Nakamura, 1977;Perkins and Weimer, 2004;Scheffe et al, 2010;Stamatiou et al, 2010;Steinfeld et al, 1999).…”
Section: Reaction Kineticsmentioning
confidence: 99%